Rice bran derived pentapeptide-induced apoptosis in human breast cancer cell models (MCF-7 and MDA-MB-231) (International Journal of Biomedical Research, 2014)
Studies have focused on the characterization of a single peptide from natural sources that contribute specific health benefits. A pentapeptide derived from rice bran has shown anti-proliferative property on human breast cancer cells. The objective of this study was to investigate the apoptotic features of pentapeptide-induced apoptosis in breast cancer cell models (MCF-7 and MDA-MB-231). The MTS (phenazine methosulfate 3-(4, 5-dimethyl thiazole-2-yl)]-2, 5-diphenyl tetrazolium bromide) assay was used to evaluate the growth inhibition activities of pentapeptide in a time-dependent manner. The apoptotic features of pentapeptide-induced apoptosis in cancerous breast cells were evaluated by morphological changes, DNA fragmentation, and caspases-3/7 activities. The levels of molecular targets (COX-2, and p53) were evaluated by ELISA kits. Pentapeptide has shown growth inhibition activity on MCF-7 and MDA-MB-231 cells. The morphological changes and DNA fragmentation were observed in pentapeptide treated MCF-7 and MDA-MB-231 cells. Significant decreases in levels ( p 0.05) of COX-2 and increases in levels ( p 0.05) of p53 were detected after treatment with pentapeptide from 72 to 96 h. The results suggest that pentapeptide inhibits growth of human breast cancer cells by introducing apoptosis and can regulate the death signal by up-regulating the level of p53 in both cells lines and down-regulating COX-2 in ER-positive MCF-7 cells.